2013
DOI: 10.1007/s10995-013-1364-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Latino Parents Choose Beverages to Serve to Infants and Toddlers

Abstract: To determine Latino parents' beliefs on the health effects of beverages on infants and toddlers, their sources of information on beverages and perceived barriers to following guidelines for healthy beverage consumption by children. We conducted 29 interviews with parents of Latino children ages 6-36 months. Parents were recruited in three community health centers in Northern California. The interviews were recorded, transcribed and analyzed using standard qualitative methods. The following dominant themes emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Lower income has been associated with higher SSB intake in prior studies (27) , and Latino and African American children in California are more likely than White children to live in poverty (28) . Other factors that may contribute to racial-ethnic disparities in child SSB consumption include increased marketing of SSB to minorities (29) , lower awareness of the health effects of SSB (30) and mistrust of local water supplies (31)(32)(33)(34) . Qualitative studies with lowincome Latino parents provide insights about beliefs and cultural factors that contribute to child intake of SSB.…”
Section: Discussionmentioning
confidence: 99%
“…Lower income has been associated with higher SSB intake in prior studies (27) , and Latino and African American children in California are more likely than White children to live in poverty (28) . Other factors that may contribute to racial-ethnic disparities in child SSB consumption include increased marketing of SSB to minorities (29) , lower awareness of the health effects of SSB (30) and mistrust of local water supplies (31)(32)(33)(34) . Qualitative studies with lowincome Latino parents provide insights about beliefs and cultural factors that contribute to child intake of SSB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative studies have also reported similar findings. 35 64–69 Preschool-aged children rely on their parents or carers for food and some children may be more vulnerable to parental unhealthy feeding habits and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,16 Beck and colleagues found that low-income Latino parents trust health care providers for nutritional information on beverages. 17 This suggests that low-income Latina immigrant mothers would be receptive to nutrition counseling and educational tools to improve their milk feeding practices. Those who provide care for children from low-income Latino immigrant families should inquire about the use of these products to prevent their excess consumption and consider the beliefs identified in this study when counseling on the use of these products.…”
Section: Discussionmentioning
confidence: 99%